Selenium testing tools cookbook : over 90 recipes to help you build and run automated tests for your web applications with Selenium WebDriver - Gundecha, Unmesh (Quick answers to common problems., 2015)
Over 90 recipes to help you build and run automated tests for your web applications with Selenium WebDriver About This Book Learn to leverage the power of Selenium WebDriver with simple examples that illustrate real-world problems and their workarounds Explains the testing of mobile applications with Appium for mobile platforms such as iOS and Android A pragmatic manual with engaging recipes and attractive screenshots to test your web applications efficiently Who This Book Is For This book is intended for software quality assurance/testing professionals, software project managers, or software developers with prior experience in using Selenium and Java to test web-based applications. This books also provides examples for C#, Python and Ruby users. What You Will Learn Understand how the locators work and use various locator methods to build reliable tests Build reliable and maintainable tests with the Selenium WebDriver API Use the PageFactory pattern to build a robust and easy to maintain test framework Build data-driven tests and extend Selenium API to implement custom steps and checks Integrate and use ATDD/BDD tools such as Cucumber, SpecFlow, Capybara, and Behave with the Selenium WebDriver API Set up iPhone/iPad and Android simulators and devices to test your mobile web application with Appium Set up Selenium Grid for faster and parallel running of tests, increasing test coverage and reducing test execution time for cross-browser testing Build extended Selenium WebDriver tests for additional coverage In Detail This book is an incremental guide that will help you learn and use the advanced features of the Selenium toolset including the WebDriver API in various situations to build a reliable test automation. You start off by setting up the test development environment and gain tips on the advanced locater strategy and the effective use of the Selenium WebDriver API. After that, the use of design patterns such as data - driven tests and PageFactory are demonstrated. You will then be familiarised with extending Selenium WebDriver API by implementing custom tasks and setting up your own distributed environment to run tests in parallel for cross-browser testing. Finally, we give you some tips on integrating Selenium WebDriver with other popular tools and testing mobile applications. By the end of this book, you will have learned enough to solve complex testing issues on your own. Style and approach This recipe-based guide covers real-life scenar...